PERINATAL NATIJALAREFFECTIVE PREPARATION OF INFERENT WOMEN WITH “THIN” ENDOMETRY FOR PREGNANCY - Komilova, D.K.; Kayumova, D.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. Infertility is a pressing problem that negatively affects reproductive health and the overall quality of life of women. According to the World Health Organization (WHO), 15-20% of women of reproductive age face the problem of infertility. Objective. In infertile women with a “thin” endometrium, it is necessary to timely identify the main causes through modern diagnostics and achieve uncomplicated pregnancy by combining PRP therapy with antiplatelet agents. Materials and methods. 80 women with primary and secondary infertility with endometrial hypoplasia were recruited. All women were of reproductive age 22-35 years. The women were divided into 2 groups: Group I consisted of 40 infertile women who underwent only antiplatelet therapy and Group II consisted of 40 women who underwent PRP therapy with antiplatelet agents. The study used general clinical, gynecological examination, UTT and Doppler, hormonal, biochemical, morphological, statistical methods. Result. In group II, where PRP-therapy was used in combination with antiplatelet agents, we achieved the expected result in 33 (82.5%) of our women. In group I, this figure was 20 (50%).